Modeling and Verification of A Novel Vector Hysteron Model - Kai DENG; Yongjian LI; Hao CHENG; Xuehai GONG; Fuyao YANG (Zhongguo dianli)
A novel implementation of a hysteresis operator in the framework of Vector Hysteron Model (VHM) is presented to describe rotational magnetization. In order to simulate the effect of anisotropy on the magnetization process more effectively, this paper changes the method of using the equipotential surface to simulate the magnetization process in the VHM model, and discusses a new scheme. This model uses the bifurcation curve as the critical surface equation of the hysteron, and uses the method of the directed bifurcation curve to solve the hysteron's critical surface equation. To further discuss the simulation performance of the model under different excitations, this paper identifies the experimental data at different frequencies, and the Moving functions are used to describe the identified parameters. The comparison between simulation results and the experimental data has been given hereafter and it is shown that the new approach is acceptable and shows good effectiveness.